Near-field resonant sensors for scanning microwave microscopy - Gordienko, Yury; Larkin, Serguei (Видавництво Львівської політехніки, 2010)
The results of numerical investigation into the most widely used versions of near-field resonant sensors for the sмм are generalized and the main concepts of their theory are formed in the report.
Keywords: Microwave microscopy; Resonant sensor; Sensitivity; Resolution